Metabolic and Cognitive Outcomes of Subchronic Once-Daily Intranasal Insulin Administration in Healthy Men - Ritze, Yvonne; Kern, Werner; Ebner, Eva-Maria; Jahn, Serena; Benedict, Christian; Hallschmid, Manfred (Frontiers in Endocrinology, 2018)
Insulin acts in the brain to limit food intake and improve memory function. We have previously shown that eight weeks of intranasal insulin delivered in four daily doses of 40 IU decrease body weight and enhance word list recall. In the present study, we investigated the effect on body composition, endocrine parameters and memory performance of eight weeks of once-daily administration of 160 IU in healthy men. We assumed that intranasal insulin administered before nocturnal sleep, a period of relative metabolic inactivity that moreover benefits memory formation, would be superior to insulin delivery in the morning and placebo administration. After a two-week baseline period, healthy male normal-weight subjects (mean age, 27.1 ± 0.9 years) received either placebo, 160 IU intranasal insulin in the morning, or 160 IU in the evening (n=12 per group) for eight consecutive weeks. Throughout the experiment, we measured body weight and body composition as well as circulating concentrations of glucose, insulin, adrenocorticotropin, cortisol, growth hormone, insulin-like growth-factor 1, adiponectin, and leptin. Declarative and procedural memory function was repeatedly assessed by means of, respectively, word list recall and word-stem priming. We found that neither morning nor evening insulin compared to placebo administration induced discernible changes in body weight and body composition. Delayed recall of words showed slight improvements by insulin administration in the evening, and serum cortisol concentrations were reduced after two weeks of insulin administration in the morning compared to the other groups. Results indicate that catabolic long-term effects of central nervous insulin delivery necessitate repetitive, presumably pre-meal delivery schedules. The observed memory improvements, although generally weaker than previously found effects, suggest that sleep after intranasal insulin administration may support its beneficial cognitive impact.